In vitro antimicrobial sensitivity of Neisseria gonorrhoeae from Rwanda. Issue 4 (August 1986) - Bogaerts, J; Vandepitte, J; Van Dyck, E; Vanhoof, R; Dekegel, M; Piot, P
Abstract : The in vitro sensitivity of 104 isolates of Neisseria gonorrhoeae to six antimicrobial agents was tested. More than 50% of the isolates produced penicillinase. Of those that did not produce penicillinase, 26% were resistant (minimum inhibitory concentration (MIC)) greater than or equal to 0.5 mg/l), and 68% showed a decreased sensitivity for penicillin G (0.06 less than or equal to MIC less than or equal to 0.25 mg/l). Twenty six per cent and 50% of the strains, respectively, showed a decreased sensitivity to thiamphenicol (MIC greater than or equal to 1 mg/l) and tetracycline (MIC greater than or equal to 2 mg/l). All isolates were sensitive to spectinomycin, kanamycin, and norfloxacin. Of 20 penicillinase producing N gonorrhoeae (PPNG) isolates examined, seven contained the 3.4 megadalton R-plasmid, another seven contained both the 3.4 megadalton and 22.5 megadalton plasmids, five the 4.3 megadalton and 22.5 megadalton plasmids, and one isolate harboured both the 3.4 and 4.3 R-plasmids, together with the 22.5 megadalton plasmid. A disturbing increase in resistance to penicillin has been observed since the publication of earlier surveys, and the clinical implications of these findings are discussed.